Soil Radon Exhalation Rate as a Function of Rainfall and Soil Suction Pressure - M. Amin, Y.; H. Mahat, R. (Malaysian Journal of Science, 2004)
It was been found that the contents of water in soil played a significant role in the rate of radon exhalation. Soil suction pressure, which is related to water content, is also related to radon exhalation rate. As the amount of rainfall increases, both the rate of radon emanation from soil and the soil suction pressure decreases. Usually, when the water content increases, landslides would occurs. In this paper, we describe our attempt at using radon emanation rate as a way of measuring slope stability.